Avaliação de um curso de informática para crianças - Dotta, Edivani Aparecida Vicente [UNESP]; Brunelli, Julia Vila Verde; Suzuki, Rafaella Barbosa [UNESP]; Maschetto, Ana Luiza Rossete [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP]; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (My University, 2013)
The aim of this study was to evaluate children’s learning outcomes after a face-to-face computer course. The study population was composed by 26 children of both genders, aged between 5 and 7 years old, from the children’s day care - CCI -“Centro de Convivência Infantil” in Portuguese, that belongs to UNESP Araraquara Campus and from Araraquara Municipal educational network CERS – “Centros de Educação e Recreação” in Portuguese. The one hour classes were completely practical, fortnightly. For children from CCI, classes were held in the Didactic Information Laboratory at Araraquara School of Dentistry – UNESP (LDI) and for those from CERs, at public schools with availability of computers that supported the systems used. Resources selected for teaching were educational games from Divertire, “Coelho Sabido” (clever bunny) line – Maternal and “Estrela Cintilante” (sparkling star) and Editora Vale das Letras – “Festa dos Dentinhos (party held for little teeth). As the course proceeded, children were visited by some of the characters from the educational games. Evaluation of the children’s learning outcomes regarding computer use was practical and was both before and after the course. Descriptive statistical analysis was performed. Participants’ performance average was calculated per point and 95% (IC95%) interval of confidence in the beginning and in the end of the course. Comparison between averages was performed by using the paired Student’s-t test. The level of significance adopted was 5%. It was observed that the children’s computer skills were significantly better after the course (Student’s-t Test: - 8.964, p<0.001). It was concluded that the evaluated course improved the children’s learning outcomes concerning computer use.

Este trabalho teve como objetivo avaliar o aprendizado de crianças após a aplicação de um curso presencial voltado para o ensino da informática. A população em estudo foi composta por 26 crianças, de ambos os sexos, com idade entre 5 e 7 anos, oriundas do Centro de Convivência Infantil (CCI) Casinha de Abelha pertencente ao Campus de Araraquara – UNESP e da Rede Municipal de Ensino de Araraquara - Centros de Educação e Recreação (CERs). As aulas na sua totalidade foram práticas, com periodicidade quinzenal e duração de uma hora cada. Para as crianças do CCI, elas aconteceram no Laboratório Didático de Informática alocado na Faculdade de Odontologia de Araraquara – UNESP (LDI) e para as do CERs em escolas públicas com computadores disponíveis que suportaram os sistemas utilizados. Os recursos selecionados para o ensino da informática neste curso foram os jogos educativos da Divertire, da linha Coelho Sabido – Maternal e a Estrela Cintilante e da Editora Vale das Letras – Festa dos Dentinhos. No decorrer do curso as crianças receberam visitas de alguns personagens pertencentes aos jogos educativos. A avaliação do aprendizado das crianças em relação à utilização do computador foi prática e ocorreu antes e após a conclusão do mesmo. Realizou-se estatística descritiva. A média de desempenho dos participantes foi calculada por ponto e por intervalo de 95% de confiança (IC95%) no momento inicial e final do curso. A comparação entre as médias foi realizada utilizando o Teste t Student pareado. O nível de significância adotado foi de 5%. Observou-se que a habilidade das crianças com o computador foi significativamente melhor após o curso (Teste t Student: -8,964, p<0,001). Conclui-se que o curso avaliado promoveu melhora no aprendizado das crianças em informática.
Evaluation of a computer course for children
Keywords: Information; Education; Children; Informática; Educação; Crianças